INSTITUTIONAL ANALYSIS OF AGROFORESTRY FARMERS TO ACHIEVE FOREST PRESERVATION IN BENDOSARI AND NGABAB VILLAGES OF PUJON, MALANG, INDONESIA - Triwanto J. (Russian Journal of Agricultural and Socio-Economic Sciences, 2022)
One of the problems faced in the management of production forest areas is related to the activities of the community around the forest to meet their daily needs. The role of Forest Village Community Institutions (LMDH) has not been maximized in forest management. Agroforestry also functions as a deterrent to soil erosion through land cover and canopy strata, storage of groundwater reserves, carbon sequestration, therefore, to reduce greenhouse gas emissions, and as a habitat for the conservation or protection of certain flora and fauna. The purpose of the study was to examine the effect of LMDH on environmentally friendly forest management. This research was conducted in March - September 2021 in the villages of Bendosari and Ngabab, Pujon, Malang Regency. The method of determining the number of respondents uses the Slovin formula. The results obtained are that the performance of LMDH Alam Sumber Makmur and LMDH Bendosari has not been able to meet the needs of the village community, there is a relationship or influence between institutions and sustainability as indicated by the correlation coefficient value of -0.810* which means it has a significant relationship of 0.015.